A prototype rapid dual energy X-ray absorptiometry (DEXA) system can predict the CT composition of beef carcases. (March 2021) - Calnan, H.; Williams, A.; Peterse, J.; Starling, S.; Cook, J.; Connaughton, S.; Gardner, G.E.
Abstract: The development of a novel rapid dual energy X-ray absorptiometry (DEXA) system provides the opportunity to improve measurement of beef carcase composition. A prototype rapid DEXA system was built in a shipping container to scan 51 beef carcases selected for a wide range in weight and fatness. One side of each carcase was spray chilled and the other conventionally chilled overnight before being quartered for DEXA scanning and then being cut into 16 pieces for CT scanning to determine carcase composition. Spray chilling did not impact DEXA prediction of CT composition, with the DEXA system describing 89%, 95%, and 87% of the variation in beef carcase CT lean %, fat % and bone %, with a root mean square error of prediction of 2.31 lean %, 2.15 fat %, and 1.12 bone % units. These results demonstrate that the novel rapid DEXA system has excellent capacity to predict CT composition in beef carcases. Highlights: Rapid DEXA described 89% and 95% of variation in beef carcase CT lean % and fat%. DEXA predicted CT lean % and fat % with a root mean square error of 2.31% and 2.15%. DEXA described 87% variation in CT bone % with a root mean square error of 1.12%. Spray chilling did not influence DEXA prediction of CT composition in beef carcases. DEXA described 14% (±7%) more variation in forequarter composition than hind.